Exovascular application of epigallocatechin-3-O-gallate-releasing electrospun poly(l-lactide glycolic acid) fiber sheets to reduce intimal hyperplasia in injured abdominal aorta. (21st September 2015) - Lee, Mi Hee; Kwon, Byeong-ju; Koo, Min-Ah; Jang, Eui Hwa; Seon, Gyeung Mi; Park, Jong-Chul
Abstract: Intimal hyperplasia is an excessive ingrowth of tissue resulting in chronic structural lesions commonly found at sites of atherosclerotic lesions, arterial angioplasty, vascular graft anastomoses, and other vascular abnormalities. Epigallocatechin-3-O-gallate (EGCG) was shown to elicit antioxidant, anti-proliferative, and anti-thrombogenic effects. In this study, we used an electrospinning technique to synthesize EGCG-eluting biodegradable poly(l -lactide glycolic acid) (PLGA) fiber sheets for local delivery of EGCG and investigated the effect of their exovascular application on intimal hyperplasia following balloon-induced abdominal aorta injury in a rabbit experimental model. The morphology of the composite sheets was characterized using scanning electron microscopy and Fourier transform-infrared spectroscopy. EGCG was loaded and dispersed into the PLGA-based electrospun fibers. The EGCG-loaded PLGA sheets exhibited sustained EGCG release following the initial 24 h of burst release in phosphate-buffered saline. In vivo studies demonstrated significant inhibition of intimal hyperplasia following the application of the EGCG-eluting electrospun PLGA fiber sheets, compared with vehicle PLGA controls. In conclusion, our results show that exovascular application of EGCG-eluting PLGA electrospun fiber sheets may provide a useful system for the effective local delivery of drugs for the prevention of intimal hyperplasia.